2022
DOI: 10.3390/ijms23168903
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Electrical Impedance as a Method to Decipher CCR7 Signalling and Biased Agonism

Abstract: The human C-C chemokine receptor type 7 (CCR7) has two endogenous ligands, C-C chemokine ligand 19 (CCL19) and CCL21, displaying biased agonism reflected by a pronounced difference in the level of β-arrestin recruitment. Detecting this preferential activation generally requires the use of separate, pathway-specific label-based assays. In this study, we evaluated an alternative methodology to study CCR7 signalling. Cellular electrical impedance (CEI) is a label-free technology which yields a readout that reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…This is in line with other studies, which report CCL21 to be significantly worse at inducing β-arrestin2 recruitment [ 21 , 22 , 23 , 26 , 27 ]. In a previous study, we obtained similar results regarding G protein activation and β-arrestin recruitment [ 24 ]. Here, we used NanoBRET instead of NanoBiT to monitor β-arrestin recruitment.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This is in line with other studies, which report CCL21 to be significantly worse at inducing β-arrestin2 recruitment [ 21 , 22 , 23 , 26 , 27 ]. In a previous study, we obtained similar results regarding G protein activation and β-arrestin recruitment [ 24 ]. Here, we used NanoBRET instead of NanoBiT to monitor β-arrestin recruitment.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, we previously reported that CCL19- and CCL21-induced distinct cellular impedance profiles and correlated this with differences in β-arrestin2 recruitment in HEK293A cells [ 24 ]. It seems, therefore, that even though no strong ligand bias was found in HEK293A cells, subtle differences in pathway activation can still manifest a difference in more physiologically relevant readouts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations